Joel: scope, genre(s), and meaning/ Ronald L. Troxel - Troxel, Ronald Lewis (Critical studies in the Hebrew Bible, 2015)
Receptions of Joel -- The composite character of Joel 1-2 -- Joel as narrative -- Eschatology in the Book of Joel -- Joel and genre